An Investigation into the Application of Artificial Intelligence for Language Teaching and Learning in Vietnam (Journal of Contemporary Educational Policies and Practices, 2025)
This study investigates teachers and students’ usage of artificial intelligence (AI) in language teaching and learning in Vietnam. Descriptive, correlational, and linear regression analyses are utilised to explore and compare perspectives of about 200 teachers and 700 students from eight universities in Vietnam on the usefulness of using AI in their teaching and learning of foreign languages. The findings show that there are very few differences in the views of both groups on the issue and that AI tools’ use for testing has the strongest impacts on language teaching and learning. However, teachers and learners’ AI competencies do not have any impact on their perceived usefulness of AI-powered tools. The study results are significant in the country’s discussion on how to use AI effectively for education in general and for language teaching and learning in particular.
Keywords: Artificial intelligence; AI-powered tools; AI competencies; language teaching and learning; usefulness; Vietnam